Study on the order target of the sporty sound quality of the vehicle exhaust noise under acceleration. (July 2019) - Yan, Fuwu; Xiao, Shenghao; Liu, Zhien; Du, Songze; Lu, Chihua
Correlational studies of order noise sample tuning and subjective evaluation test of sound quality were conducted to achieve sporty sound quality and confirm the correlation between the auditory sense (subjective) and the order noise level (objective) of vehicle exhaust noise under acceleration. First, the frequency range and the order ingredient of sporty quality noise were confirmed by a study of ear-hearing subjective feeling on the basis of physiological acoustics. By using an order tuning software that was developed independently, the second, fourth, and sixth order noise A-weighting sound pressure level (dB(A)) of the exhaust noise of an objective vehicle were tuned segmentally into numerous sound samples. Furthermore, samples with high sporty sound quality were selected through subjective evaluation, and the A-weighting sound pressure level (dB(A)) distributions of the second, fourth, and sixth order noise of these samples were analyzed. Consequently, the relative size relations of the second, fourth, and sixth order noise of all the exhaust noise with sporty sound quality were determined. In addition, the curve distribution zones of the corresponding order noise were formed and the order quantitative target of the sporty sound quality was considered. Finally, four passenger vehicles with representative sound qualities (sporty, quiet, and characterless) on the market were selected as the benchmark vehicles; their order noise was objectively tested and their sound qualities subjectively evaluated. Meanwhile, the order noise objective test result was compared with the order target. Results showed that when the fourth and sixth order noise curves relative to the second order noise curves were within the order target zones at most of the engine speeds, the exhaust noise of the vehicle had considerable sporty sound quality; otherwise, it did not have such a sound. Therefore, the order target of the sporty sound quality was accurate and effective.